Densely packed polymer/boron nitride composite for superior anisotropic thermal conductivity. (12th October 2017) - Zhu, Zhijia; Wang, Pengxiang; Lv, Peng; Xu, Tianhao; Zheng, Jiajin; Ma, Chen; Yu, Kehan; Feng, Wei; Wei, Wei; Chen, Liangyao
Abstract : High heat conduction performance of electrical insulating composite is highly desired in thermal management of electronics. In this study, densely packed boron nitride (BN) composites with resin matrices of epoxy, polymethyl methacrylate, and an acrylic copolymer based binder were prepared through a solvent mediated mixing and compression molding method. The solvent mediated mixing assisted homogeneous dispersion; the compression molding removed excessive resin and led to alignment of BN flakes with high filler content. The resulted composites exhibited superior in‐plane thermal conductivity k // up to 21.3 W/mK and pronounced anisotropic heat conduction properties. The thermal conductivity was positively correlated with density ρ of a specimen in experimental. A presentation of thermal conductivity k = k ρ was proposed, and the dependence of thermal conductivity on specimen density d k ( ρ ) / d ρ   >   0 was proven mathematically. The application of BN composite in LED thermal management was demonstrated. An epoxy/BN heat spreader was used to efficiently cool down a 0.3‐W LED. The cooling effect was close to that with Al board heat spreader. POLYM. COMPOS., 39:E1653–E1658, 2018. © 2017 Society of Plastics Engineers